E-BOOK TEACHING MATERIALS IMPROVE IPAS LEARNING OUTCOMES OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Fitri Wahyuningsih; Barokah Isdaryanti (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2026)
This study is driven by the use of less creative and dynamic teaching methods, which lead to inferior learning results by making pupils easily bored and struggling to comprehend the subject matter. The purpose of this project is to create Heyzine-assisted e-book instructional materials and to assess their viability and efficacy in improving fourth-grade students' learning outcomes. Research and development (R&D) using the ADDIE model is the methodology. Data-gathering procedures include observation, interviews, questionnaires, documentation, and pretests and posttests. The results of the assessment by experts, teachers and students show that the instructional materials are highly practical. The improvement in student learning results demonstrates the efficacy of the instructional materials. The pretest and posttest have normal distributions and indicate a substantial difference, with an N-Gain value of 0.7123 in the high category. The developed e-book can serve as an alternative interactive instructional medium to enhance student engagement in IPAS learning at SDN Bendan Ngisor, Semarang City.